Advances in artificial intelligence applications in the field of lung cancer - Yang, Di; Miao, Yafei; Liu, Changjiang; Zhang, Nan; Zhang, Duo; Guo, Qiang; Gao, Shuo; Li, Linqian; Wang, Jianing; Liang, Si; Li, Peng; Bai, Xuan; et al. (Frontiers in Oncology, 2024)
Lung cancer remains a leading cause of cancer-related deaths globally, with its incidence steadily rising each year, representing a significant threat to human health. Early detection, diagnosis, and timely treatment play a crucial role in improving survival rates and reducing mortality. In recent years, significant and rapid advancements in artificial intelligence (AI) technology have found successful applications in various clinical areas, especially in the diagnosis and treatment of lung cancer. AI not only improves the efficiency and accuracy of physician diagnosis but also aids in patient treatment and management. This comprehensive review presents an overview of fundamental AI-related algorithms and highlights their clinical applications in lung nodule detection, lung cancer pathology classification, gene mutation prediction, treatment strategies, and prognosis. Additionally, the rapidly advancing field of AI-based three-dimensional (3D) reconstruction in lung cancer surgical resection is discussed. Lastly, the limitations of AI and future prospects are addressed.